A combined continuous microflow photochemistry and asymmetric organocatalysis approach for the enantioselective synthesis of tetrahydroquinolines - Sugiono, Erli; Rueping, Magnus (Beilstein Journal of Organic Chemistry, 2013)
A continuous-flow asymmetric organocatalytic photocyclization–transfer hydrogenation cascade reaction has been developed. The new protocol allows the synthesis of tetrahydroquinolines from readily available 2-aminochalcones using a combination of photochemistry and asymmetric Brønsted acid catalysis. The photocylization and subsequent reduction was performed with catalytic amount of chiral BINOL derived phosphoric acid diester and Hantzsch dihydropyridine as hydrogen source providing the desired products in good yields and with excellent enantioselectivities.
Keywords: asymmetric transfer hydrogenation; binolphosphate; continuous-flow reactors; flow chemistry; microreactors; organocatalysis; photochemistry